Corticospinal tract abnormalities and ventricular dilatation: A transdiagnostic comparative tractography study - Sarica, Alessia; Quattrone, Andrea; Mechelli, Alessandro; Vaccaro, Maria Grazia; Morelli, Maurizio; Quattrone, Aldo (NeuroImage clinical, 2021)
•PSP patients can show marked ventricular enlargement (PSP-vd).•PSP-vd patients had increased FA and AxD in CST regions close to lateral ventricles.•CST alterations in PSP-vd are due to CST compression by the enlarged ventricles.•CST alterations in PSP-vd are similar to those found in NPH but of lesser degree.•Higher ventriculomegaly is associated with higher severity of the CST alterations. Microstructural alterations of corticospinal tract (CST) have been found in idiopathic normal pressure hydrocephalus (iNPH). No study, however, investigated the effect of ventricular dilatation on CST in Progressive Supranuclear Palsy (PSP). The aim of this study was to investigate CST diffusion profile in a large cohort of PSP patients with and without ventricular dilatation. Twenty-three iNPH patients, 87 PSP patients and 26 controls were enrolled. Evans index (EI) and ventricular volume (VV) were measured in all patients. CST tractography was performed to calculate FA, MD, AxD and RD in six different anatomical regions: medulla oblungata (MO), pons (P), cerebral peduncle (CP), posterior limb of internal capsule (PLIC), corona radiata (CR), subcortical white matter (SWM). ANCOVA was used for comparing CST diffusion profiles between the groups and association between CST microstructural metrics and measures of ventricular dilatation (EI and VV) was assessed. Thirty-three PSP patients had ventricular dilatation (EI > 0.30, PSP-vd) while 54 PSP patients had normal ventricular system (EI ≤ 0.30, PSP-wvd). iNPH patients had the most marked FA and AxD increase in PLIC and CR of CST followed by PSP-vd, PSP-wvd and controls; RD was altered only in iNPH. A strong correlation was found between CST diffusion metrics and EI or VV. Our findings confirm the microstructural changes of CST in iNPH patients and demonstrate for the first time similar alterations in PSP-vd patients, suggesting a crucial role of ventricular dilatation in the mechanical compression of CST.